SURVEI PERMAINAN DAN OLAHRAGA TRADISIONAL DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (PENJASORKES) - Septaliza, Dewi; Victorian, Richard (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
The purpose of this study is to investigate traditional games and sports in learning penjasorkes. Samples are 8 elementary schools Ogan Komering Ilir. The sampling technique used the random sampling. Collecting data in this study using a survey method. Data collection techniques in this study is documentation and questionnaires. Analysis of the data used is descriptive with percentage. Conclusion games and traditional sports in penjasorkes learning on students in elementary schools throughout Ogan Komering Ilir, amounting to 8 primary school quite well as evidenced by the distribution of instructional time by 79.66%, the ability of teachers in the mastery of the material and learning penjasorkes are classified as good by 84 , 20%, characteristics of the game as well as the motion generated by both criteria that is equal to 74.03%, the elements penjasorkes classified as very good by 83.59% and interest in sports games traditionally classified as good by 83.26.